Assessing Decision-making Capacity: The Interpretation and Implementation of the Mental Capacity Act 2005 Amongst Social Care Professionals. Issue 1 (1st January 2016) - Murrell, Anna; McCalla, Leona
Abstract : The Mental Capacity Act, 2005 (MCA) provides a statutory framework for assessing an individual's decision-making capacity and for making best interests decisions on behalf of those who lack capacity. This study explores how the MCA is understood and interpreted by social care practitioners, with specific reference to assessing decision-making capacity. It was complete across four adult health and social care teams in the south-west of England, semi-structured interviews were completed with six social work practitioners. The findings suggest that the interpretation of the principles and criteria for assessing capacity varies and that assessing decision-making capacity can often be a complex process; assessments are often part and parcel of numerous interdependent processes and competing demands. It is necessary to ensure that the different processes are carried out separately and sequentially in order to promote objective capacity assessments. The study outlines the key responsibilities that the local authority has with regards to the implementation of the MCA.